Center-related Bias in MELD Scores Within a Liver Transplant UNOS Region: A Call for Standardization. Issue 7 (July 2020) - Verna, Elizabeth C.; Connelly, Charles; Dove, Lorna M.; Adem, Patricia; Babic, Nikolina; Corsetti, James; Faix, James; Hayden, Joshua A.; Lifshitz, Mark; Stotler, Brie; Jin, Zhezhen; Mohan, Sumit; et al.
Abstract : Background: Model for End-Stage Liver Disease (MELD) score–based liver transplant allocation was implemented as a fair and objective measure to prioritize patients based upon disease severity. Accuracy and reproducibility of MELD is an essential assumption to ensure fairness in organ access. We hypothesized that variability in laboratory methodology between centers could impact allocation scores for individuals on the transplant waiting list. Methods: Aliquots of 30 patient serum samples were analyzed for creatinine, bilirubin, and sodium in all transplant centers within United Network for Organ Sharing (UNOS) region 9. Descriptive statistics, intraclass correlation coefficients (ICCs), and linear mixed-effects regression were used to determine the relationship between center, bilirubin, and calculated MELD-sodium (MELD-Na) score. Results: The mean MELD-Na score per sample ranged from 14 to 38. The mean range in MELD-Na per sample was 3 points, but 30% of samples had a range of 4–6 points. Correlation plots and intraclass correlation coefficient analysis confirmed bilirubin interfered with creatinine, with worsening agreement in creatinine at high bilirubin levels. Center and bilirubin were independently associated with creatinine reported in mixed-effects models. Unbiased hierarchical clustering suggested that samples from specific centers have consistently higher creatinine and MELD-Na values. Conclusions: Despite implementation of creatinine standardization, centers within a single UNOS region report clinically significant differences in MELD-Na on an identical sample, with differences of up to 6 points in high MELD-Na patients. The bias in MELD-Na scores based upon center choice within a region should be addressed in the current efforts to eliminate disparities in liver transplant access. Abstract : Supplemental Digital Content is available in the text.